2019
DOI: 10.1186/s12985-019-1136-6
|View full text |Cite
|
Sign up to set email alerts
|

Tropism and molecular pathogenesis of canine distemper virus

Abstract: Background Canine distemper virus (CDV), currently termed Canine morbillivirus , is an extremely contagious disease that affects dogs. It is identified as a multiple cell tropism pathogen, and its host range includes a vast array of species. As a member of Mononegavirales , CDV has a negative, single-stranded RNA genome, which encodes eight proteins. Main body Regarding the molecular pathogenesis, the hemagglutinin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
96
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 100 publications
(120 reference statements)
0
96
0
8
Order By: Relevance
“…Many studies have proved that the H protein plays a pivotal role in eliciting the protective immune response during CDV infection (Bhatt et al, 2019). The H protein contains cytotoxic T lymphocyte epitopes that induce cytotoxic T lymphocytes (CTL) antiviral activity in animals and has become a target for developing novel genetically engineered vaccines (Rendon-Marin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have proved that the H protein plays a pivotal role in eliciting the protective immune response during CDV infection (Bhatt et al, 2019). The H protein contains cytotoxic T lymphocyte epitopes that induce cytotoxic T lymphocytes (CTL) antiviral activity in animals and has become a target for developing novel genetically engineered vaccines (Rendon-Marin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To date, there has been no evidence of a human infection by CDV; however, it was reported that CDV was isolated from a human cancer cell line [305]. In addition, further investigation is required to determine whether CDV can initiate a cross-species event in humans because of virus adaption [306].…”
Section: Discussionmentioning
confidence: 99%
“…Its 15,690-nt viral genome encodes six open reading frames (ORFs) corresponding to six proteins: nuclear protein (N), phosphoprotein (P), matrix protein (M), fusion protein (F), hemagglutinin protein (H), and large protein (L) (Martinez-Gutierrez and Ruiz-Saenz 2016; Sidhu et al 1993). Of these proteins, CDV H and F glycoproteins are located on viral particle surfaces and are responsible for virus attachment to host cells and fusion with the host cell membrane (Rendon-Marin et al 2019). Importantly, several previous studies have shown that the F protein is a highly conserved immunogenic protein and an important antigen for inducing neutralizing antibodies against CDV (David et al 2019).…”
Section: Introductionmentioning
confidence: 99%